Mabadiâ Asyroh Nalar Fikih Sosial Ali Yafie - Yulianto, Y (SHAHIH: Journal of Islamicate Multidisciplinary, 2017)
Making a decision in Islamic law must be contextual and give a priority to ummaâs benefit (mashlahat) and consider a sense of justice.Â  This purpose portraysÂ the main thought of Ali Yafieâs social fiqh. This research uses a descriptive qualitative method to see social fiqh. The result of this research shows that Ali Yafieâs social fiqh thought by taking mabadiâ asyroh (ten principles) which are: (1) hadul ilmi is methodological process and product of legislation of Islamic law; (2) maudluâul ilmi is identification of social problems; (3) tsamrotul ilmi is ummaâs benefits; (4) fadlul ilmi is obligation of each Moslem; (5) nisbatul ilmi is maqashid al-syariah and fardlu âain- fardlu kifayah considerations; (6) wadliâul ilmi is KH. A. Sahal Mahfudz dan K.H. Ali Yafie, (7) ismul ilmi is social fiqh, (8) istimdadul ilmi is Alquran, hadith, al-ijmaâ, qiyas, rational-holistic integration, reality, and interpreting Islamic texts based on social benefits (mashlahah), (9) hukmul ilmi is wajib kifayah and wajib âain, and (10) masailul ilmi, is any social problems.Â